2007
DOI: 10.1007/s11325-007-0137-7
|View full text |Cite
|
Sign up to set email alerts
|

Armodafinil improves wakefulness and long-term episodic memory in nCPAP-adherent patients with excessive sleepiness associated with obstructive sleep apnea

Abstract: Residual excessive sleepiness (ES) and impaired cognition can occur despite effective and regular nasal continuous positive airway pressure (nCPAP) therapy in some patients with obstructive sleep apnea (OSA). A pooled analysis of two 12-week, randomized, double-blind studies in nCPAP-adherent patients with ES associated with OSA evaluated the effect of armodafinil on wakefulness and cognition. Three hundred and ninety-one patients received armodafinil (150 or 250 mg) and 260 patients received placebo once dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 45 publications
1
70
0
1
Order By: Relevance
“…[78][79][80] Modafinil and armodafinil are generally well tolerated in patients with OSA. [81][82][83][84] It is important to note, however, that neither modafinil nor armodafinil addresses the underlying obstruction that causes OSA and must be used in conjunction with CPAP to avoid the return of symptoms and cardiovascular complications. Patients should be counseled to ensure compliance with CPAP when using adjunctive pharmacotherapy.…”
Section: Evaluation and Treatment Of Residual Esmentioning
confidence: 99%
“…[78][79][80] Modafinil and armodafinil are generally well tolerated in patients with OSA. [81][82][83][84] It is important to note, however, that neither modafinil nor armodafinil addresses the underlying obstruction that causes OSA and must be used in conjunction with CPAP to avoid the return of symptoms and cardiovascular complications. Patients should be counseled to ensure compliance with CPAP when using adjunctive pharmacotherapy.…”
Section: Evaluation and Treatment Of Residual Esmentioning
confidence: 99%
“…Armodafinil is a longer acting R-enantiomer of modafinil, both Federal Drug Administration approved wakefulness promoting drugs to treat OSA patients who are compliant on CPAP therapy but continue to have excessive daytime sleepiness [24]. The mechanism of action remains unknown to date, but is felt to be related to the orexin wakepromoting neurotransmitter system.…”
Section: Pharmacotherapiesmentioning
confidence: 99%
“…Some of the known side effects include rash, hypertension, headache, nausea, and psychiatric symptoms such as anxiety, depression, mania and psychosis. Compliance on CPAP does become an issue as well, as patients started on wake promoting medications are also noted to become less compliant on CPAP therapy [2,[24][25][26].…”
Section: Pharmacotherapiesmentioning
confidence: 99%
“…[37][38][39][61][62][63] A summary of the results of these clinical trials is given in Tables 2 and 3. In addition, there are two ongoing open-label trials of armodafi nil: one in trial-naïve patients (with narcolepsy, OSA, or SWD) and one extension study in patients who completed any of the randomized trials and were able to participate for 12 months or longer.…”
Section: Clinicalmentioning
confidence: 99%
“…In addition, episodic secondary memory was signifi cantly improved at the fi nal visit in patients taking armodafi nil (p = 0.0102 versus placebo). 62 Pooled analyses of the results of these two studies 63 demonstrated that at the fi nal visit, sleep latency was increased by 2.0 minutes with armodafi nil versus a decrease of 1.5 minutes for placebo (p Ͻ 0.0001). Furthermore, patients treated with armodafi nil had improved wakefulness later in the day (at the last three MWT assessments at 1500, 1700, and 1900 hours) compared with placebo (+1.1 minutes versus −0.3 minutes, respectively; p Ͻ 0.05).…”
Section: Narcolepsymentioning
confidence: 99%